Kinerja Instansi Pemerintah Daerah Berdasarkan Pengaruh Akuntabilitas Dana BOK, Mutu Pelayanan Publik, dan Komitmen Organisasi terhadap Kinerja Puskesmas : (Studi Kasus pada Puskesmas Grogol, Sukoharjo) - Armawandani, Anisa; Dewi, Maya Widyana; Suprihati (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2025)
This study aims to analyze the effect of accountability in managing the Health Operational Assistance (BOK) fund, public service quality, and organizational commitment on the performance of local government institutions at Puskesmas Grogol, Sukoharjo Regency. A quantitative approach was employed with 55 respondents selected through probability sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression. The results indicate that accountability and organizational commitment have a significant positive effect on employee performance, whereas public service quality has no significant effect. Simultaneously, the three variables affect performance with an adjusted R² value of 0.321. These findings emphasize that improving public institution performance is not solely determined by service quality but also by strong accountability systems and employee commitment. This study provides practical implications for local governments to strengthen public fund management and foster a committed work culture to enhance the quality of public health services.